Exploring the Concepts of Abstinence and Recovery through the Experiences of Long-Term Opiate Substitution Clients. Issue 2 (April 2015) - Notley, Caitlin; Blyth, Annie; Maskrey, Vivienne; Pinto, Hayley; Holland, Richard
Background: This study aimed to explore the client experience of long-term opiate substitution treatment (OST). Methods: A qualitative grounded theory study set in a UK rural community drug treatment service. Results: Continuous OST enabled stability and a sense of "normality." Participants expressed relief at moving away from previous chaotic lifestyles and freedom from the persistent fear of opiate withdrawal. However, for some, being on a script made them feel withdrawn, lethargic, and unable to fully participate in mainstream society. Intrapersonal barriers (motivation and fear) were perceived as key barriers to abstinence. Conclusions: Participants experienced long-term OST as a transition between illicit drug use and recovery. Recovery was seen as a process rather than a fixed goal, confirming that there is a need for services to negotiate individualized recovery goals, spanning harm minimization and abstinence-oriented treatment approaches.